2017
DOI: 10.3390/cells6010003
|View full text |Cite
|
Sign up to set email alerts
|

Implications for Diverse Functions of the LINC Complexes Based on the Structure

Abstract: The linker of nucleoskeleton and cytoskeleton (LINC) complex is composed of the outer and inner nuclear membrane protein families Klarsicht, Anc-1, and Syne homology (KASH), and Sad1 and UNC-84 (SUN) homology domain proteins. Increasing evidence has pointed to diverse functions of the LINC complex, such as in nuclear migration, nuclear integrity, chromosome movement and pairing during meiosis, and mechanotransduction to the genome. In metazoan cells, the nuclear envelope possesses the nuclear lamina, which is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
25
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(26 citation statements)
references
References 85 publications
0
25
0
1
Order By: Relevance
“…Another case for higher-order organization of LINC complex involves how nuclei move rearward in wounded NIH3T3 fibroblasts. During nuclear migration, linear arrays of SUN2-Nesprin -2G LINC complexes, termed transmembrane actinassociated nuclear (TAN) lines, assemble to tether the nuclei to moving actin cables [9,31]. As a more extreme example, LINC complex proteins involved in meiotic chromosome dynamics and telomere bouquet formation redistribute and concentrate in large patches associated with chromosome ends [6,[46][47][48].…”
Section: Other Factors That Influence Force Transmission Through Lincmentioning
confidence: 99%
See 2 more Smart Citations
“…Another case for higher-order organization of LINC complex involves how nuclei move rearward in wounded NIH3T3 fibroblasts. During nuclear migration, linear arrays of SUN2-Nesprin -2G LINC complexes, termed transmembrane actinassociated nuclear (TAN) lines, assemble to tether the nuclei to moving actin cables [9,31]. As a more extreme example, LINC complex proteins involved in meiotic chromosome dynamics and telomere bouquet formation redistribute and concentrate in large patches associated with chromosome ends [6,[46][47][48].…”
Section: Other Factors That Influence Force Transmission Through Lincmentioning
confidence: 99%
“…It has also been proposed that a cysteine adjacent to the SUN domain of SUN1 protein is able to form intermolecular disulfide bonds with neighboring SUN trimers [44,50]. The specific requirement of mammalian SUN1, but not SUN2, during meiotic chromosome pairing, might be associated with the ability of SUN1 to more easily form higher-order structures than SUN2 [9,43,44,49]. Interestingly, a recent study has shown different mechanisms involved in homeostatic nuclear positioning under centrifugal force.…”
Section: Other Factors That Influence Force Transmission Through Lincmentioning
confidence: 99%
See 1 more Smart Citation
“…The LINC complex was discovered relatively recently, but has been shown to be highly conserved in eukaryotes, with myriad functions as described in numerous reviews [4][5][6][7][8][9]. These LINC-mediated functions include regulation of nuclear shape and position [10,11], mechanosensory signal transduction [12], control of cell division, intranuclear architecture and gene regulation [13][14][15], and the specialized behavior of meiotic chromosomes to ensure segregation and fertility [16][17][18].…”
Section: Introductionmentioning
confidence: 99%
“…For chromosome motion during meiotic prophase I, the LINC complex transmits cytoskeleton‐driven forces to the telomeres and thus to chromosomes. The LINC complex also plays a role in nuclear positioning and migration in somatic cells (Hieda, ).…”
Section: Introductionmentioning
confidence: 99%